'Mr Peel's Amendments' in New South Wales: Imperial Criminal Reform in a Distant Penal Colony. Issue 2 (3rd May 2016) - Ford, Lisa; Roberts, David Andrew
ABSTRACT: This article investigates the difficult interface between metropolitan legal reform and empire in the late 1820s. In 1828, the Supreme Court of New South Wales sentenced dozens of men to death under legislation that had been repealed in Britain. It then insisted that every one of them be set free. This mess raised a fundamental question agitated in different ways around the empire in that decade: to what degree should colonial subjects enjoy the benefits of modernized metropolitan criminal law? Even as successive local and metropolitan Acts imposed new constraints on the civil rights of convicts in New South Wales, the Supreme Court insisted that even the most notorious recidivists in the colony should be protected against the Bloody Code from the moment it was reformed at home. In doing so, the court ignored the terms of section 1 of the Criminal Statutes Repeal Act passed at the request of a former East India Company officer to preserve the operation of the Code in India. Thus the peculiar reception controversy in New South Wales shows not only how disruptive metropolitan reform could be for colonies, it performed a growing racial gap in the imagination of legal subjecthood in different corners of empire.